Diagnostic and clinical perspectives of fusion imaging in cardiology: is the total greater than the sum of its parts?. Issue 1 (30th December 2005) - Bax, J J; Beanlands, R S; Klocke, F J; Knuuti, J; Lammertsma, A A; Schaefers, M A; Schelbert, H R; Von Schulthess, G K; Shaw, L J; Yang, G Z; Camici, P G
Abstract : Positron emission tomography, cardiovascular magnetic resonance and multislice computed tomography have contributed to changing our pathophysiological understanding of many conditions. Clinically, they have provided new tools for the identification of preclinical disease and a better understanding of how disease progresses. The application of these imaging modalities to preclinical disease and the use of these techniques in patients with overt cardiovascular disease are reviewed.